The Phytochemical Analysis of Hay Infusions and Papaya Leaf Juice as an Attractant Containing Insecticide for Aedes Aegypti - Cahyati, Widya Hary; Asmara, Widya; Umniyati, S Rahmah; Mulyaningsih, Budi (Jurnal Kesehatan Masyarakat, 2017)
Aedes aegypti mosquito population could be controlled by using lethal ovitrap. The addition of hay infusions as a attractant greatly enhance Aedes aegypti eggs trapped, and papaya leaf juice may inhibit Aedes aegypti eggs evolve to larvae or a larvae to pupae stage. This study was conducted to find out the chemical compounds in hay infusion and papaya leaf juice. We used phytochemical test using UV-Vis Spectrophotometry, Thin Layer Chromatography, and High Performance Liquid Chromatoraphy (HPLC) method. The results showed that hay infusion contains 12,75 mg/L ammonium and <1,20 ppm (Âµg/mL) lactic acid and papaya leaf juice contains 0,25% alkaloid, 0,14% flavonoid, 0,30% saponin, â¤68 mg/L steroid and 11,34% tannin, but negative terpenoid. We concluded that hay infusion and papaya leaf juice contains chemical compounds that could be use as attractant and bioinsecticide to Aedes aegypti, respectively.